Instructive scaffolds for tissue engineering - Lin, Jin (2015)
Polycaprolactone (PCL) is widely used in tissue engineering, primarily as a scaffold material to support cells and direct cellular ingrowth. However, native PCL is generally passive, and lack appropriate cues to direct cell response. This issue may be addressed by incorporating cell-instructive cues into the scaffolds. In this project, Poly (lactic-co-glycolic acid) (PLGA) microspheres were incorporated into PCL scaffolds as a biomolecule delivery vehicle. It was hypothesized that the PLGA micro-particles will be taken up by adherent cells, and delivers their biological payload in cyto. To test this hypothesis, Poly (lactic-co-glycolic acid) micro-particles containing Calcein-AM (CAM/PLGA MPs) were fabricated via single emulsion and evaluated for uptake efficiency. It was observed that PLL coating was necessary for cellular uptake, through electrostatic interactions between the carriers and the cell membrane. To study the use of PLGA micro-particles to modify gene expression, PLGA micro-particles carrying siRNA against GFP (SiRNA/PLGA MPs) were fabricated via double emulsion technique. Similar to the previous results, siRNA was found to be effectively delivered to adherent cells, resulting in reduction of GFP signal. Lastly, CAM/PLGA MPs were mixed with PCL powder and fabricated into films via heat press. Adherent cells were again found to have reduced GFP signals, demonstrating knockdown of GFP, and suggests the potential application as an instructive scaffold.